Sobre curvas invariantes no bordo do bilhar hexagonal elíptico. - Cássio Henrique Vieira Morais (2016)
In this work we discuss the hexagonal string billiard, introduced by Fetter. Numerical experiments suggests a possible integrability of the billiard map, contradicting Birkhoff’s Conjecture in C^2 case. We give a proof of Hubacher’s Theorem about invariant curves and we discuss an exemple due to Halpern about a C^2 convex curve, with non vanishing curvature such that there is no rotational invariant curve for the billiard map in a neighborhood of the boundary.